ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA PADA MATERI MATRIKS DITINJAU DARI SELF-EFFICACY - Apriliya; Mochamad Abdul Basir (Pusat Penelitian dan Pengembangan Reka Karya Amerta (REKARTA), 2019)
This research is to find out and analyze the mathematical creative thinking ability of class XI students in MA N 1 Semarang on matrix material in terms of self-efficacy. The research method used is descriptive qualitative. The instrument used was a test instrument on the matrix material with a total of 4 description items and a non-test instrument in the form of a self-efficacy questionnaire with 20 statements. The research sample was 33 students of class XI in MA N 1 Semarang City. The results of this study are that there is a relationship between self-efficacy and students creative thinking abilities on the Matrix material. Judging from the percentage of achievement based on the level of self-efficacy, if self-efficacy is high then the ability to think creatively is also high. Achievement of the percentage of indicators of creative thinking ability according to the level of self-efficacy in a row from high, medium, low, namely fluency, flexibility, elaboration, elaboration. Overall, the achievement of the ability to think creatively gets a percentage of 66.56%.